2022
DOI: 10.1177/09636625211065743
|View full text |Cite
|
Sign up to set email alerts
|

Mapping mental models of science communication: How academics in Germany, Austria and Switzerland understand and practice science communication

Abstract: The mental models that individual scholars have of science communication – how it works, what it is supposed to achieve and so on – shape the way these academics actually communicate to the public. But these mental models, and their prevalence among scholars, have rarely been analysed. Drawing on a large-scale, representative web survey of academics at universities in Germany, Austria and Switzerland ( n = 15,778) from 2020, we identify three mental models that are prevalent among scholars, and that correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
1
11
0
6
Order By: Relevance
“…For example, Burchell found that participatory approaches to science communication was considerably higher in fields like the arts, humanities, and social sciences compared to the STEM (Science, Technology, Engineering, and Mathematics) fields [ 116 ]. Similar results are also reported by Kessler and colleagues, with scientists from the humanities, social sciences, and life sciences being more likely to adhere to dialogue and participatory perspectives [ 21 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…For example, Burchell found that participatory approaches to science communication was considerably higher in fields like the arts, humanities, and social sciences compared to the STEM (Science, Technology, Engineering, and Mathematics) fields [ 116 ]. Similar results are also reported by Kessler and colleagues, with scientists from the humanities, social sciences, and life sciences being more likely to adhere to dialogue and participatory perspectives [ 21 ].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, while Howell and colleagues [ 115 ] found that both late and early career scientists held positive views on the role of social media in providing opportunities to engage with the public, our respondents’ focus nevertheless remained on deficit-oriented goals when asked about their social media science communication goals. While we can only speculate that perhaps the differences between the academic contexts of the Netherlands and of the United States might be the underlying cause of these differences, further research comparing academic contexts and science communication approaches among scientists (much like the one conducted by Kessler and colleagues [ 21 ]) could shed more light on the issue.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is part of the author's research agenda working with the ZSoA to investigate the distribution and consequences of researchers' perceived pressure. To date, the following papers addressing, among other things, aspects of the wider research agenda on the distribution and consequences of researchers' perceived pressure have been published or submitted for peer review : Johann, Raabe et al (2021), Johann, Rathmann, et al (2021, and Kessler et al (2022).…”
Section: Appendix A: Additional Tablesmentioning
confidence: 99%